Biomedical therapy using synthetic WKYMVm hexapeptide. (2nd April 2016) - Choi, Young Hwan; Jang, Il Ho; Heo, Soon Chul; Kim, Jae Ho; Hwang, Nathaniel S.
ABSTRACT: WKYMVm hexapeptide has been identified as a strong FPR2 agonist through a library screening of synthetic peptides. The FPR2 has been reported to play a crucial role in inflammation and angiogenic responses via stimulation of chemotaxis, migration, cell proliferation, wound healing and vessel growth. Recently, the therapeutic effects of WKYMVm have been reported in various disease models. In cutaneous wound model in diabetic mice, WKYMVm facilitated wound healing processes by stimulating the formation of capillary and arteriole and re-epithelialization. In coronary artery stenosis model, WKYMVm coating on stent promoted re-endothelialization and lowered restenosis rate. In hindlimb ischemia mouse model, intramuscular injection of WKYMVm promoted homing of exogenously transplanted endothelial colony-forming cells and neovascularization, resulting in salvaging hindlimb. Furthermore, a single injection of WKYMVm encapsulated in poly (lactide-co-glycolide) microspheres was demonstrated to be as efficient as multiple injections of WKYMVm in restoring blood flow in hindlimb ischemia model. These observations may open up promising biomedical applications of WKYMVm for tissue repairs and regenerations.